Plasma Activation of Polyethylene Powder - Šourková, Hana; Špatenka, Petr (Polymers, 2020)
Polyethylene powder of average particle diameter of 160 µm was activated in a plasma reactor made from aluminum of volume 64 dm3 at the pressure 100 Pa. Dense oxygen plasma was sustained with a microwave discharge powered by a pulsed magnetron source of power 1 kW mounted onto the top flange of the plasma reactor. Polymer powder was treated in a batch mode with 0.25 kg/batch. The powder was placed into a stainless-steel dish mounted in the center of the reactor where diffusing plasma of low ion density, and the O-atom density of 2 × 1021 m-3 was sustained. The powder was stirred in the dish at the rate of 40 rpm. The evolution of powder wettability versus treatment time was measured using the Washburne method, and the surface composition was determined by X-ray Photoelectron Spectroscopy (XPS). The wettability versus the oxygen concentration assumed a parabolic behavior. The maximal oxygen concentration, as revealed by XPS, was 17.5 at.%, and the maximal increase of wettability was 220%. The efficiency of O-atoms utilization in these experimental conditions was about 10% taking into account the spherical geometry of dust particles and perfectly smooth surface. The method is scalable to large industrial systems.
Keywords: plasma treatment; batch mode treatment; polymer powder; surface activation